Combating Antifungal Resistance in Dermatophytes: A Multidisciplinary Approach Integrating Essential Oil Nanoformulations, Community Health Strategies, and Pharmacological Innovation - Muhammad Hassam Rehm, Muhammad Saeed Raza, Zahida Perveen, Javeria Sarfraz, Zobia Mushtaq, Nadeem Akhtar Korai, Madiha Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: To investigate antifungal resistance in dermatophytes and evaluate the efficacy of essential oil (EO)-based nanoformulations as novel therapeutics. Study Duration: January 2022 to March 2023. Study Place: Community Medicine Department, District Headquarters (DHQ) Hospital, Sargodha, Pakistan. Study Type: Experimental (in vitro and ex vivo). Methodology: 120 dermatophyte isolates from tinea infections (corporis, cruris, pedis).Antifungal susceptibility testing (terbinafine, fluconazole, griseofulvin).Development of clove and tea tree oil nanoemulsions.Efficacy testing via MIC assays and ex vivo nail models. Results: 68% resistance to terbinafine, 52% to fluconazole.Clove oil nanoemulsions achieved MIC ≤0.5 µg/mL against 85% resistant strains.Ex vivo nail models showed 92% mycological cure. Discussion: EO nanoformulations bypass resistance via biofilm disruption and enhanced bioavailability. Conclusion: Nanoemulsions are promising alternatives to conventional antifungals. Keywords: Antifungal resistance, dermatophytes, essential oils, nanoformulations, terbinafine.